2006
DOI: 10.1167/iovs.05-0962
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Light Damage: Structural and Functional Effects of the Antioxidant Glutathione Peroxidase-1

Abstract: The data showing increased oxidative damage in baseline GPx-deficient retina give rise to the hypothesis that increased oxidative stress provides a "preconditioning" environment in which protective mechanisms paradoxically render GPx1-deficient retinas less vulnerable to light-induced oxidative damage. This study identified glutaredoxin-2 as a potential candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…The approximately 20% of residual GPx1 expression in the GPx1 KO retinas was most likely due to background and/or nonspecific primer amplification as previously described in the same animal model. 24 There was a significant increase of GPx1 gene expression in the ROP WT retina compared to the sham WT retina, which was not observed in GPx1 KO retinas. In contrast, GPx2, GPx3, and GPx4 gene expression was not altered across all experimental groups (see Supplementary Material and Supplementary Figs.…”
Section: Retinal Antioxidant Gene Expressionmentioning
confidence: 83%
See 1 more Smart Citation
“…The approximately 20% of residual GPx1 expression in the GPx1 KO retinas was most likely due to background and/or nonspecific primer amplification as previously described in the same animal model. 24 There was a significant increase of GPx1 gene expression in the ROP WT retina compared to the sham WT retina, which was not observed in GPx1 KO retinas. In contrast, GPx2, GPx3, and GPx4 gene expression was not altered across all experimental groups (see Supplementary Material and Supplementary Figs.…”
Section: Retinal Antioxidant Gene Expressionmentioning
confidence: 83%
“…15 GPx has previously been reported to play important roles in protecting the retina from phototoxicity 24,30 and cataract formation. 31 The GPx enzyme family consists of four selenium-dependent isoforms, GPx1, GPx2, GPx3, and GPx4.…”
Section: Discussionmentioning
confidence: 99%
“…Knock-out mice of antioxidant enzymes created to date include SOD1 Ϫ/Ϫ mice (12) and GPx1 Ϫ/Ϫ mice (11). Both SOD1 and GPx1 localize in the cytosol, not mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…However, their essentiality has remained unclear. Although several studies have reported the knock-out mice of antioxidant enzymes, they have not shown severe photoreceptor cell abnormality or degeneration (11,12). This is probably because multiple antioxidant enzymes share target substrates; thus compensating for each other.…”
mentioning
confidence: 99%
“…Retinal damage due to excessive exposure to solar radiation or intense artificial sources of light has been demonstrated in a number of studies (Kirkness 1986;Gosbell, Stefanovic et al 2006). However, while several epidemiologic studies support the role of chronic exposure to sunlight in the development of AMD (Taylor, West et al 1992;Delcourt, Carriere et al 2001), the acceptance that chronic exposure to less intense light sources plays a role in retinal injury is still controversial.…”
Section: Motivation and Purposementioning
confidence: 99%